Symposium: New horizons in the treatment of type 1 diabetes mellitus. Automated insulin infusers: bomechanical artificial pancreas? - Luis Grosembacher (Revista de la Sociedad Argentina de Diabetes, 2021)
The exponential increase in the prevalence of diabetes mellitus (DM) throughout the world also includes the increase in people with type 1 diabetes (T1D)1. This disease is characterized by the autoimmune and progressive destruction of pancreatic Beta cells, causing an endogenous insulin insufficiency and hyperglycemia that can only be controlled by exogenous insulin administration.